EVALUATION OF IMPLEMENTATION OF LEARNING QUALITY ASSURANCE IN SMA MUHAMMADIYAH 2 YOGYAKARTA - Desi Arafatun Na’mah; Abdullah Taman (Jurnal Pendidikan Akuntansi Indonesia, 2016)
The objective of this study is to describe and examine the evaluation of the implementation of the Quality Assurance of Learning Activities is seen in terms of the efforts made to ensure the quality of learning, supporting and restricting factors of quality assurance in activities learning at class XI in SMA Muhammadiyah 2 Yogyakarta. This research uses qualitative descriptive approach. Data were collected through observations, interviews and documentation. Results showed that (1) The efforts that SMA Muhammadiyah 2 Yogyakarta conducted to guarantee the quality of learning activities in class XI were preparation of the learning tools, supervision of class, quality management system ISO 9001:2008, convene a workshops, evaluation of the learning activities, and monitoring of the learning process by the school principal. (2) The factors that support the implementation of the quality assurance activity learning class XI in SMA Muhammadiyah 2 Yogyakarta were the school facilities, involvement of teachers and learners while carrying out the learning process in the class, the encouragement and warning from teachers to students, coordination between the parents of class XI students with the school, the evaluation meeting with the school committee, regular meetings between the head of the SMA Muhammadiyah 2 Yogyakarta with Dikdasmen good area or region.Keywords: Quality Assurance, SMA Muhammadiyah 2 Yogyakarta